The analysis of the EFL Students’ Speaking Performances in Learning English by Recorded WhatsApp Video Call - Diana Fauzia Sari; Nurrahma Wati; Tgk Maya Silviyanti (Indonesian TESOL Journal, 2026)
This study focused on teaching speaking skills using Recorded WhatsApp Video Call as a treatment for the first grade of one public senior high school in Banda Aceh, Indonesia. Researchers used a purposive sampling by consulting with the English teacher. The samples taken were class X IPA 3 (Science class) consisting of 20 students. Researchers performed a sequential explanatory mixed-method study that displayed a descriptive analysis of quantitative data collection and an in-depth understanding through qualitative data collection. This study compared the result of the students’ achievement in speaking before and after the treatment. The instruments used were an oral speaking test and interview. The data were analysed by using statistic simple formula and gathered from pre-tests and post-tests. The result showed that students’ speaking skills improve after implementing the method. The students had a positive response towards the use of WA video call in a learning activity despite internet access limitation that the students face.